Clay Mineral Alteration in Oil and Gas Fields: Integrated Analyses of Surface Expression, Soil Spectra, and X-Ray Diffraction Data - Tri Muji Susantoro; Asep Saepuloh; Fitriani Agustin; Ketut Wikantika; Agus Handoyo Harsolumakso (Canadian Journal of Remote Sensing, 2020)
Subsurface hydrocarbon occurrences can be detected by clay mineral (CM) alteration at the surface as a consequence of hydrocarbon migration. This study analyzed CM alteration in an oil and gas (O&G) field in the West Tugu field, located in the northwest Java Basin of Indonesia. Landsat 8 OLI data acquired on 25 September 2015 and soil spectral reflectance (SSR) data recorded using analytical spectral devices (ASD) in March 2017 were processed using clay indices to analyze CM alteration. Soil samples from a field survey of the same area were also analyzed using X-ray diffraction (XRD) to identify their CM compositions. CM distribution was empirically modeled by integrating the SSR bands re-sampled to Landsat 8 OLI (SSRL) bands and the CM composition using the best subset regression method and regression analyses. The resulting model was applied to Landsat 8 OLI images to map the surface CM alteration. The results show that CM alteration observed in the O&G field is an indicator of hydrocarbon microseepage at the surface. These results can be used as a technique to identify prospective regions that contain hydrocarbons and differentiate from those that are barren, and could be useful for increasing the rate of drilling success.